”Sleeps and wakes with viticulture”: Peasant and post-peasant farming in the light of sustainability, using the example of Villány viticulture - Balogh, Pál Géza; Kurucz, Réka (POLARITIES, 2023)
Over the past decades, the meeting of ecology and ethnography and anthropology has resulted in a flourishing new research field, ethnobiology and ethno-ecology, the study of traditional ecological knowledge and local knowledge. The question of these research findings and their adaptation is becoming increasingly important as trends in the ecological crisis intensify. After a general introduction, the present paper presents the results of research into small-scale peasant viticulture in the Villány wine-growing region using ethnographic fieldwork tools in the period 1940-1960. It attempts to interpret the local knowledge and farmers’ attitudes from the point of view of sustainability and environmental protection, and raises the question of the usability of certain knowledge today.